Corporate Liability for Environmental Crimes in Industrial Supply Chains: A Criminal and Administrative Law Approach - Rani Eka Arini; Salwa Aulia Novitasari; Almira Ulimaz (West Science Law and Human Rights, 2026)
This study analyzes corporate liability for environmental crimes within industrial supply chains in Indonesia through a normative legal approach integrating criminal and administrative law perspectives. The research examines the adequacy of the existing legal framework, particularly Law No. 32 of 2009 on Environmental Protection and Management, in addressing corporate accountability for environmental harm. By applying statutory, conceptual, and case approaches, this study identifies key challenges in enforcement, including difficulties in proving corporate intent, fragmentation of responsibility within supply chains, and the predominance of administrative sanctions over criminal prosecution. The findings indicate that although Indonesian law formally recognizes corporate criminal liability and incorporates strict liability principles, practical implementation remains limited due to evidentiary constraints, institutional weaknesses, and regulatory gaps. Furthermore, the complexity of industrial supply chains enables corporations to diffuse responsibility through subcontracting and outsourcing practices. This study proposes an integrated liability model that strengthens coordination between criminal and administrative enforcement, expands corporate responsibility across supply chains, and enhances the deterrent effect of sanctions. The study contributes to legal scholarship by offering a holistic framework for corporate environmental accountability and provides policy recommendations to support sustainable industrial governance in Indonesia.